(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article deals with the origin of the suffix -ище (-išče) and its derivatives -ovišče/-evišče, -лище, -нище, characterizes the peculiarities of their functioning in the Common Slavonic language and ancient Russian-Ukrainian language; it has been proved that the high productivity of this suffix laid down the basis for its increased activity in subsequent periods of language development.